Macrophages and cancer stem cells: a malevolent alliance - Paola Allavena; Elisabeth Digifico; Cristina Belgiovine (Molecular Medicine, 2021)
Abstract Myeloid cells infiltrating tumors are gaining ever growing attention in the last years because their pro-tumor and immunosuppressive functions are relevant for disease progression and therapeutic responses. The functional ambiguity of tumor-associated macrophages (TAMs), mostly promoting tumor evolution, is a challenging hurdle. This is even more evident in the case of cancer stem cells (CSCs); as active participants in the specialized environment of the cancer stem cell niche, TAMs initiate a reciprocal conversation with CSCs. TAMs contribute to protect CSCs from the hostile environment (exogenous insults, toxic compounds, attacks from the immune cells), and produce several biologically active mediators that modulate crucial developmental pathways that sustain cancer cell stemness. In this review, we have focused our attention on the interaction between TAMs and CSCs; we describe how TAMs impact on CSC biology and, in turn, how CSCs exploit the tissue trophic activity of macrophages to survive and progress. Since CSCs are responsible for therapy resistance and tumor recurrence, they are important therapeutic targets. In view of the recent success in oncology obtained by stimulating the immune system, we discuss some macrophage-targeted therapeutic strategies that may also affect the CSCs and interrupt their malevolent alliance.